(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: The research is based on the assessment of the beneficial role of vitamin E (vit-E) supplementation on the reproductive and renal functions in Cadmium (Cd)-exposed male mice. Materials and Method: Mice (n = 15 in each group) were kept untreated (Group A) or fed with cadmium chloride (CdCl2 ) (3.5 mg/kg, Group B) per day or both CdCl2 (3.5 mg/kg) with vit-E supplementation (200 mg/kg, Group C) daily for 60 days. Mice were euthanized, blood samples were collected, and serum was prepared for biochemical and hormonal analysis. Sperm motility, sperm concentration, testis weight, and diameter were taken. Tissues from the kidneys and testicles were collected in 10% neutral buffered formalin for histotexture study. Results: Cd treatment reduced the serum thyroxine (T4 ) and testosterone levels, but vit-E supplementation increased both T4 and testosterone levels in the Cd-treated mice. Cd treatment decreased sperm motility and concentration, testicular weight, and diameter, and induced degenerative changes in the seminiferous tubules, which significantly improved upon vit-E supplementation. Increased serum urea, uric acid, and creatinine concentrations, along with cellular infiltration in the renal tubular epithelium and glomerular hyperplasia, were found in the Cd-treated mice, which were not found in the vit-E-supplemented mice. Conclusion: The study points to the harmful consequences of Cd on reproductive performance and renal functions that could potentially be mitigated upon vit-E supplementation in the diet. J. Adv. Vet. Anim. Res., 11(4): 1057–1065, December 2024 http://doi.org/10.5455/javar.2024.k857